Two butterfly species of rare and specious genus Teinopalpus Hope, 1843 in Vietnam - Lien, Vu Van (Academia Journal of Biology, 2012)
In the world, the genus Teinopalpus has two species: T. aureus and T. imperialis. Both of them occur in Vietnam. They are high important conservation butterfly species of Vietnam. Some studies on the genus indicated that each species have two subspecies. However, the differences between subspecies have not been indicated. The differences in morphology of species in different locations of Vietnam are checked through specimens. Specimens were collected in the North: Vinh Phuc, Lao Cai, and Ha Giang provinces; in Central highland: Kon Tum, Lam Dong and Dak Nong provinces. The result received by checking specimens shows that of T. aureus in North (Vinh Phuc) differs from those from Central high land (Lam Dong and Dak Nong) by cell of hind wings and outer margin of forewings. Two subspecies are T. aureus shinkai in North Vietnam and T. aureus eminens in center from Ha Tinh, Khanh Hoa to the Central highland (Lam Dong, Dak Nong). The specimens of Teinopalpus imperialis do not differ among different locations of Vietnam. The subspecies in Vietnam is T. imperialis imperatrix. The species T. imperialis distributes higher altitude than T. aureus and further to the South Vietnam than the species T. imperialis. Both species in Vietnam are rare with scattered small populations in moderate and high forest altitudes of Vietnam where natural forests have been disturbed. Their distribution areas on mountain natural forests are scattered and isolated in Vietnam and it is very rare to see these species on mountains of their distribution areas. Due to high commercial value, they have been collected for sell. Both natural forest destruction of and over-collecting can threaten these butterfly species. To preserve these species, the natural forests in mountains of their distribution areas must be protected or the buttflies can be bred for conservation. Key to the species and subspecies of the genus Teinopalpus 1(4).  The postdiscal yellow patch on the hindwing of the male covers about ½ of the cell; the discal line on the hindwing of both sexes curves inward at the basal area. 2(3).  The line near the wing base lies inside of the point of wing vein 6 and cell (the yellow patch of this subspecies is bigger than this of subspecies T. a. eminens).................................T. aureus shinkai (Fig. 1) 3.       The line near the wing base lies adjacent to the point of wing vein 6 and cell (the yellow patch of this subspecies is smaller than this of subspecies T. a. sinkai)..................................T. aureus eminens (Fig. 2) 4.       The postdiscal yellow patch on the hindwing of the male enters only a small distal area of cell; the discal line on the hindwing of both sexes is more or less straight or slightly wavy...T. imperialis imperatrix (Figs. 3)